Clinical Profiles of Obstructive Hydrocephalus in Patient with Von Hippel–Lindau - Naqeeb, Mohammed R.; Abdulmannan, Dina M. (Majalah Kedokteran Bandung, 2024)
Von-Hippel-Lindau (VHL) is an autosomal dominant disease that affects multiple systems that may result in benign and malignant multisystem tumors. The estimated incidence of VHL is 1 in 36,000 births. Disease incidence ranges from 10 to 40 years, with an average of 26 years, and it impacts diverse ethnic groups. VHL results from mutations in the germ line that have been mapped to chromosome 3P25. Currently, this is the only gene known to cause the syndrome. This study presented a case of obstructive hydrocephalus in a patient with VHL. A 19-year-old female was referred to the Eye Clinic for a diagnosis of papilledema. She began to experience vagal abdominal discomfort for no apparent reason. Per exam, the patient had 20/20 OD and 20/400 OS, with an intraocular pressure of 14 OU. The patient's MRI revealed a posterior fossa cranial cystic brain lesion that was obstructing the fourth ventricle and causing obstructive hydrocephalus. Early detection, management, and focal laser treatment of capillary hemangiomas in the retina's periphery led to favorable visual outcomes. Even after vitreoretinal surgery, the tumors may cause exudative retinal detachment and have an inferior visual prognosis if left untreated.